Minimally Invasive Subtemporal Intradural Approach for Penetrating Orbitocranial Injury by Wooden Foreign Body Into the Lateral Wall of the Cavernous Sinus - Avraham, Elad; Smolikov, Alexander; Smolyakov, Rozalia; Azriel, Amit; Sufaro, Yuval; Kaisman-Elbaz, Tehila; Zlatin, Gregory; Melamed, Israel (Frontiers in Surgery, 2020)
Transorbital penetrating head injuries are relatively rare, though potentially fatal injuries. Trajectory for intracranial entrance is typically via the orbital roof, the superior orbital fissure, or the optic canal. Those injuries are surgically challenging and may require versatile neurosurgical approaches. Here, we report the case of a 71-year-old male who sustained a penetrating transorbital injury after a fall, by a wooden fragment, which passed through the superior orbital fissure (SOF) to the lateral wall of the ipsilateral cavernous sinus. This patient presented fully conscious (GCS15) with ocular related complaints (periorbital edema, ophthalmoplegia and blindness for the injured eye), and was surgically removed by minimally invasive subtemporal approach. Complete removal of the foreign body was achieved with no major surgical complications. We reviewed the literature to discuss the radiological diagnosis, multidisciplinary approach in management and appropriate treatment options for these kind of injuries from a neurosurgical perspective (with emphasis on minimally invasive techniques).